Mystic weed, Parthenium hysterophorus: threats, potentials, and management - Khairul Bashar, H. M.; Juraimi, Abdul Shukor; Ahmad Hamdani, Muhammad Saiful; Uddin, Md Kamal; Asib, Norhayu; Anwar, Md. Parvez; Rahaman, Ferdoushi (MDPI, 2021)
Parthenium hysterophorus is an invasive weed species that competes aggressively with other plants and is also allelopathic. It poses a significant risk to human health, livestock, the environment, soil, and agriculture. However, given some clinical studies, its potential for antidiabetic, antioxidant, antitumor, herbicidal, pesticidal, and antimalarial therapies should be researched further in attempts to discover more relevant applications. It can be used as a nutrient-dense, readily available, and cheap fertilizer. Parthenium can also be used as an herbicide, an insecticide, and a phyto-remedial mediator to extract metals and dyes from agricultural waste. Here we provide basic information on the morphology, reproduction, environmental impacts, and management of this species. Effects of methanol, ethanol, hexane, acetone, and aqueous (water) Parthenium extracts are described. Because P. hysterophorus is said to be one of the world’s seven worst weeds, some control measures, including mechanical, chemical, cultural, and biological control, are discussed. The allelopathy of this weed is difficult to regulate, and there are both positive and negative interactions between Parthenium and other species due to allelochemical action. Several toxic phenolic compounds produced by P. hysterophorus are responsible for weed suppression, and we discuss details of their mode of action and potential applications.